2016
DOI: 10.2135/cropsci2014.08.0546
|View full text |Cite
|
Sign up to set email alerts
|

Plant Characteristics of High‐Yielding Upland Rice Cultivars in West Africa

Abstract: In West Africa, upland rice (Oryza spp.) is typically grown in low‐input production systems under low soil fertility conditions. Genetic improvement may offer a cost‐effective approach to improving the productivity rather than approaches that rely solely on external nutrient inputs. In the 1990s, the upland rice breeding program of the West Africa Rice Development Association (now Africa Rice Center [AfricaRice]) developed New Rice for Africa (NERICA) cultivars. However, recent studies suggest that there is sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…poor soil fertility and heavy weed infestation. Since the publication of that paper, there have been many reports supporting this argument in West Africa (Saito, 2014(Saito, , 2016Saito & Futakuchi, 2014;Sito, Dieng, Vandamme, et al, 2015;Saito, Vandamme, Segda, et al, 2015;Vandamme et al, 2016a;Vandamme et al, 2016b). In East and Southern Africa, good performance of upland NERICA varieties has been frequently observed in field trials and on farm (Kijima et al, 2008;Sekiya et al, 2013;Shrestha et al, 2012).…”
Section: Martinez Et Al (2014) Review Rice Breeding Activities In Latinmentioning
confidence: 96%
See 3 more Smart Citations
“…poor soil fertility and heavy weed infestation. Since the publication of that paper, there have been many reports supporting this argument in West Africa (Saito, 2014(Saito, , 2016Saito & Futakuchi, 2014;Sito, Dieng, Vandamme, et al, 2015;Saito, Vandamme, Segda, et al, 2015;Vandamme et al, 2016a;Vandamme et al, 2016b). In East and Southern Africa, good performance of upland NERICA varieties has been frequently observed in field trials and on farm (Kijima et al, 2008;Sekiya et al, 2013;Shrestha et al, 2012).…”
Section: Martinez Et Al (2014) Review Rice Breeding Activities In Latinmentioning
confidence: 96%
“…Similar to results from Asia (Asai et al, 2009;Atlin et al, 2006;Saito et al, 2007), Saito and Futakuchi (2009), Saito et al (2012) identified B6144-F-MR-6-0-0 (an indica variety developed in Indonesia) as a potential donor for improving yield under low-input conditions. Aus257 was identified as early maturing and high yielding, with strong weed-suppressive ability and greater nutrient uptake than NERICA 1 (Saito, 2016;Saito & Futakuchi, 2014). IR 74371-3-1-1 (an indica variety developed in the Philippines) showed higher nutrient-use efficiency than NERICA 1, which contributed to higher yield in low-input conditions (Saito, 2016).…”
Section: Martinez Et Al (2014) Review Rice Breeding Activities In Latinmentioning
confidence: 99%
See 2 more Smart Citations
“…3 and 4). Saito (2015) reported that grain yield per N uptake, that is, nitrogen-use efficiency (NUE), was lower in NERICA 1 than in other rice varieties (Aus 257 and IR 74371-3-1-1). Although N uptake was not determined in the present study, NUE may be lower in NERICA 1 than in BW196.…”
Section: Discussionmentioning
confidence: 99%